A map of the rubisco biochemical landscape - Noam Prywes; Naiya R. Phillips; Luke M. Oltrogge; Sebastian Lindner; Leah J. Taylor-Kearney; Yi-Chin Candace Tsai; Benoit de Pins; Aidan E. Cowan; Hana A. Chang; Renée Z. Wang; Laina N. Hall; Daniel Bellieny-Rabelo; et al. (Nature, 2025)
Abstract Rubisco is the primary CO 2 -fixing enzyme of the biosphere 1 , yet it has slow kinetics 2 . The roles of evolution and chemical mechanism in constraining its biochemical function remain debated 3,4 . Engineering efforts aimed at adjusting the biochemical parameters of rubisco have largely failed 5 , although recent results indicate that the functional potential of rubisco has a wider scope than previously known 6 . Here we developed a massively parallel assay, using an engineered Escherichia coli 7 in which enzyme activity is coupled to growth, to systematically map the sequence–function landscape of rubisco. Composite assay of more than 99% of single-amino acid mutants versus CO 2 concentration enabled inference of enzyme velocity and apparent CO 2 affinity parameters for thousands of substitutions. This approach identified many highly conserved positions that tolerate mutation and rare mutations that improve CO 2 affinity. These data indicate that non-trivial biochemical changes are readily accessible and that the functional distance between rubiscos from diverse organisms can be traversed, laying the groundwork for further enzyme engineering efforts.